2020
DOI: 10.3390/su12156214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Perceived Value of Ecosystem Services on Tourists’ Behavioral Intentions for Aogu Coastal Wetland

Abstract: This research empirically tested the effect of perceived value of ecosystem services on tourists’ intentions to revisit the Aogu coastal wetland in Taiwan. Data were collected using a structured survey and structural equation modeling was then done to test the research hypotheses. Based on the data collected from 230 tourists in the Aogu coastal wetland, the perceived value of ecosystem services of wetland has a positive effect on tourists’ environmental concerns and friendly environmental behavior. Results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
(100 reference statements)
1
15
0
Order By: Relevance
“…In the literature, it is also evidenced [49] that the perceived value of the ecosystem services of wetlands has a positive effect on the environmental concerns of tourists and ecological behavior; in this study, the authors prove the effectiveness of the perceived value of wetlands and ecosystem services on tourists' intentions to revisit Taiwan's Aogu Coastal Wetlands.…”
Section: Perceived Value Satisfaction and Loyalty In Coastal And Mari...mentioning
confidence: 51%
“…In the literature, it is also evidenced [49] that the perceived value of the ecosystem services of wetlands has a positive effect on the environmental concerns of tourists and ecological behavior; in this study, the authors prove the effectiveness of the perceived value of wetlands and ecosystem services on tourists' intentions to revisit Taiwan's Aogu Coastal Wetlands.…”
Section: Perceived Value Satisfaction and Loyalty In Coastal And Mari...mentioning
confidence: 51%
“…Personal values affect the level of satisfaction and outcomes of student behavior (Kumar, 2018). The value of behavioral beliefs, when attitudes toward perceived values increase through friendly environmental behavior, the value of behavioral ideas leads to increased behavioral intentions (M. T. Lee et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Determinants of intention, attitude toward behavior, social norms or social pressures, and perceived behavioral control all increase when aware of environmental issues, increasing their intention to take actions that support the environment. (M. T. Lee et al, 2020). Thus, this approach with the movement of subtle values can be an effort to improve the anomaly of community behavior and become a real solution in minimizing poverty in disadvantaged areas.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding ecotourism, it is possible to find several academic studies. Some studies focus on ecotourism as a learning tool (Mondino, Beery, 2019), role of ecotourism in sustainable tourism development (Salman et al, 2020), ecotourism potential of destinations (Safarabadı, 2016;Güler, 2021), carrying capacity within ecotourism (Butarbutar, Soemarno, 2013;Zhao, Jiao, 2019)planningand design (Shang et al, 2020;Sisriany,Furuya, 2020;Aryal et al, 2019;Cohen, Silva, 2010), research topics benefiting from meta-analysis (Wondirad, 2019), tourists' intention to participate in ecotourism (Pham, Khanh, 2020;Ren et al, 2021;Lee et al, 2020;Handriana, Ambara, 2016), intentions of locals/residents toparticipate in ecotourism (Wu, Chen, 2018;Landra et al, 2018;Mogoria et al, 2018;Lim et al, 2017;Wanga et al, 2013;Menon, 2019;Adeleke, 2015;Zhang, Lei, 2012). Mondino and Beery (2019) have investigated ecotourism as a learning tool benefiting from a case study and have found out that ecotourism activities supported collaboration between stakeholders, but because of insufficient environmental education (language, method, and course related problems at higher governmental levels) there were still negative perceptions of the sides.…”
Section: Ecotourismmentioning
confidence: 99%
“…The results coming from the sample consisting of 406 tourists have underlined that environmental knowledge is very important and has a positive effect on environmental attitudes, environmental perceived value, and perceived consumption effectiveness. Lee et al (2020) have conducted a study about the effects of perceived value of ecosystem services on tourists' behavioural intentions and have found out that perceived value of ecosystem services have positive effect on both tourists' behaviour and environmental concerns. Handriana and Ambara (2016) have investigated responsible environmental behaviour intention of tourists in Indonesia.…”
Section: Ecotourismmentioning
confidence: 99%